Professions and discipline functional and conflict perspectives - Rossides, Daniel W. (Prentice Hall, 1998)
This unique book provides a comprehensive evaluation that asks if our professions perform social functions and solve widespread social problems or merely the problems of upper-level individuals and groups? The book presents the effect of corporate world-market capitalism on professions reflected in the corporate squeeze on doctors, for example. It demonstrates the fallacies of professional claims of objectivity, unique knowledge bases, value-neutrality, altruism, and nonpartisanship. It demonstrates that professions are integral components of the American class system and highlights the stratification within professions and their reliance on subordinate and exploited labor. It shows the widespread and persistent racial, ethnic, and gender stratification in all professions along with recent studies showing that similarly qualified minorities are not rewarded equally. The book also includes full chapters on the policy professions; professional deviance; and the depiction of professions in the mass media. An essential reference book for any reader who wishes a greater understanding of the problems of class in the United States.